Comparison of Helicobacter pylori Detection Using Immunohistochemistry and Giemsa and Its Association with Morphological Changes in Active Chronic Gastritis - Wildawati Nurdin; Ening Krisnuhoni; Kusmardi Kusmardi (The Indonesian Society for Digestive Endoscopy, 2016)
Background: Gastritis is an inflammation of the gastric mucosa as a response to infection or irritation of the gaster. The most common aetiology of chronic gastritis is Helicobacter pylori (H. pylori) infection. Presence of H. pylori is associated with the occurrence of inflammation, atrophy, and intestinal metaplasia. In terms of morphology, H. pylori is known in 2 forms, which are rod-shaped and coccoid-shaped. Coccoid-shaped bacteria are difficult to detect using Giemsa staining. Therefore, immunohistochemistry staining of H. pylori and evaluation of the sensitivity of coccoid-shaped of H. pylori are needed.Method: Cross-sectional study on 90 biopsy tissues of chronic gastritis patients in year 2015 and 2014, which included 30 Giemsa cases with positive H. pylori, 30 cases of active chronic gastritis with negative H. pylori but coccoid-shaped was found, and 30 non-active chronic gastritis, were subsequently stained with immunohistochemistry staining of H. pylori.Results: Expression of coccoid-shaped H. pylori in active chronic gastritis was significantly different (p 0.05) in immunohistochemistry staining. There was a significant difference between active chronic gastritis with positive H. pylori and negative H. pylori in immunohistochemistry staining with degree of inflammation. Sensitivity and specificity test between Giemsa and immunohistochemistry staining showed sensitivity of 65% and specificity of 100%.Conclusion: Immunohistochemistry staining in active chronic gastritis was more sensitive compared to Giemsa staining in detecting H. pylori, particularly the coccoid-shaped bacteria.